1999
DOI: 10.1123/pes.11.2.129
|View full text |Cite
|
Sign up to set email alerts
|

Sport Participation and Perceived Academic Performance of School Children and Youth

Abstract: School children and youth from Primary Grade 5 to Secondary Grade 7 (average age range, 9 to 18 years) in Hong Kong completed a sports participation questionnaire and rated their own academic performance (AP). Results of ANOVAs indicated that frequency and extent of participation tended to be significantly higher for students with high self-ratings than for students with less satisfactory self-reported performance, and that this trend was significantly stronger in females than males and present in all age grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0
8

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 19 publications
4
41
0
8
Order By: Relevance
“…This relationship was true, regardless of culture . These gender differences in sport identity and sport participation may be influenced by the societal tradition for females to be less assertive than males (Curry & Weiss, 1989;Lindner, 1999) . This phenomenon, which could be considered universal, was thought to produce passive attitudes in females, especially when considering sport identity and sport participation .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This relationship was true, regardless of culture . These gender differences in sport identity and sport participation may be influenced by the societal tradition for females to be less assertive than males (Curry & Weiss, 1989;Lindner, 1999) . This phenomenon, which could be considered universal, was thought to produce passive attitudes in females, especially when considering sport identity and sport participation .…”
Section: Discussionmentioning
confidence: 97%
“…This phenomenon, which could be considered universal, was thought to produce passive attitudes in females, especially when considering sport identity and sport participation . In Chinese culture, men are expected to be physically stronger than women (Lindner, 1995(Lindner, , 1998(Lindner, , 1999 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Snyder (1989) and Synder and Sprietzer (1977) report a positive relationship between sport and academic performance, and others have illustrated a link between physical education/exercise and academic performance (Keller, 1982;Shephard, 1997;Thomas, Landers, Salazar and Etnier, 1994), while others have concluded that there is no meaningful evidence for such links (Hauser and Lueptow, 1978). In a Hong Kong based study of the relationship between self-perceived academic performance and participation in sports, Lindner (1999) concluded that students with more confidence in their academic ability were the group with stronger motives for involvement in sports and physical activities. However, he stated that no causal relationship could be deduced from this data as there was no evidence that regular exercise causes good academic performance, or that lack of exercise or excessive participation causes poor school results (Lindner, 1999).…”
Section: 2mentioning
confidence: 99%
“…In a Hong Kong based study of the relationship between self-perceived academic performance and participation in sports, Lindner (1999) concluded that students with more confidence in their academic ability were the group with stronger motives for involvement in sports and physical activities. However, he stated that no causal relationship could be deduced from this data as there was no evidence that regular exercise causes good academic performance, or that lack of exercise or excessive participation causes poor school results (Lindner, 1999).…”
Section: 2mentioning
confidence: 99%